Trends in Housing Research in Türkiye: A Bibliometric Analysis (Third Sector Social Economic Review, 2025)
Housing is not merely a physical structure that meets individuals’ shelter needs; it is also a fundamental component in ensuring social justice, building societal welfare, and promoting sustainable urbanization. Increasing population, urbanization pressure, economic fluctuations, and disaster risks have rendered the housing issue a multidimensional and high-priority policy area. However, it is observed that systematic evaluations of academic production in the field of housing in Türkiye remain limited. Therefore, this study aims to map the existing literature and identify future research areas by conducting a bibliometric analysis of master’s and doctoral theses written between 1986 and 2025 in Türkiye. A total of housing keyword-based 1,997 theses obtained from the Council of Higher Education Thesis Center database were analyzed according to various criteria such as thesis title, subject area, academic discipline, institution, and year of production. The analysis conducted using MAXQDA-24 software reveals that the majority of studies are concentrated in architecture and interior architecture disciplines. Although housing studies exhibit a multidisciplinary character, the need for increased research on sustainability, the right to housing, disaster risk, and social inclusion is emphasized. This study aims to guide future interdisciplinary research in areas such as disadvantaged groups, housing accessibility, and green building practices, while also offering evidence-based insights to inform policy-making processes.
Keywords: Housing; Real Estate; Bibliometric Analysis; Prisma; MAXQDA-24